2021
DOI: 10.31235/osf.io/4wzx7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the Health Outcomes of Conditional Cash Transfer Program in Rural Philippines

Abstract: The Pantawid Pamilya Pilipino Program (4Ps), the first conditional cash transfer (CCT) program of the Philippine government, has become a popular approach aimed at improving the health and educational status of disadvantaged households. Its implementation is expected to advance the government’s health agenda, particularly in terms of child mortality reduction and maternal health improvement. Despite the growing evidence on the positive health outcomes resulting from the implementation of CCT programs, evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…9 The 4Ps conditionalities include attending maternal and child health care services, as well as participation in monthly Family Development Sessions that cover topics on health, wellbeing, family dynamics, and parenting. [9][10][11] Upon completion, participants are entitled to cash transfers and food subsidies that could support food security and improvements to housing conditions. 9,10 Overall, a combination of both the conditionalities and entitlements are expected to provide families with the resources to create healthy environments that are supportive of children's nutritional status.…”
Section: Introductionmentioning
confidence: 99%
“…9 The 4Ps conditionalities include attending maternal and child health care services, as well as participation in monthly Family Development Sessions that cover topics on health, wellbeing, family dynamics, and parenting. [9][10][11] Upon completion, participants are entitled to cash transfers and food subsidies that could support food security and improvements to housing conditions. 9,10 Overall, a combination of both the conditionalities and entitlements are expected to provide families with the resources to create healthy environments that are supportive of children's nutritional status.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the institutionalisation of 4Ps and its positive evaluations, the program has also faced criticism for design and implementation challenges (Tabuga and Reyes, 2012;Peñalba, 2019). For example, the periodic targeting strategy of 4Ps may exclude newly eligible households from the program (Albert and Dacuycuy, 2017;Economic Policy Research Institute, 2019;Dadap-Cantal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Others have noted the small size of the cash grant relative to the income of poor households is not enough to result in meaningful impacts (Tabuga and Reyes, 2012;Economic Policy Research Institute, 2019). Concern has also been raised over the capacity of partner institutions to implement the program; for example, some health facilities serving 4Ps beneficiaries have limited capacity, making it challenging to monitor compliance with health-related conditionalities (Fernandez and Olfindo, 2011;Peñalba, 2019). Additionally, an evaluation of the outcomes of 4Ps by the Institute of Family Life and Children's Studies (2016) found that 4Ps may contribute to community division in settings where there is confusion or mistrust in the identification and inclusion of 4Ps beneficiaries (Institute of Family Life and Children's Studies, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations